Analysis of the diagnostic efficacy of ultrasound, MRI, and combined examination in benign and malignant breast tumors - Ma, Dianpei; Wang, Changliang; Li, Jie; Hao, Xiaohan; Zhu, Yun; Gao, Zhizhen; Liu, Chun; Luo, Changfan; Huang, Yu (Frontiers in Oncology, 2025)
BackgroundTo compare the diagnostic effectiveness of ultrasound (US), magnetic resonance imaging (MRI), and their combined application in distinguishing between benign and malignant breast tumors, with particular emphasis on evaluating diagnostic performance in different breast densities—fatty breast tissue, where fat predominates, and dense breast tissue, which contains a significant amount of fibroglandular tissue.Materials and methodsA retrospective analysis was conducted on 185 patients with breast tumors, including 90 malignant and 95 benign cases. All patients underwent both US and MRI examinations within one week prior to surgery. The diagnostic accuracy of US, MRI, and their combined use in differentiating benign and malignant tumors was evaluated.ResultsThe combined examination demonstrated the highest area under the curve (AUC), sensitivity, and negative predictive value (NPV) (0.904, 90%, 90.4%), outperforming US (0.830, 73.3%, 78.6%) and MRI (0.897, 89.7%, 88.8%). DeLong test results revealed statistically significant differences in AUC between US and MRI, as well as between US and the combined examination (P < 0.05). However, the difference in AUC between MRI and the combined examination was not significant (P = 0.939). In patients with fatty breast tissue, no significant differences were found between MRI and US, or between MRI and the combined examination (P = 0.708 and P = 0.317, respectively). However, the diagnostic performance between US and the combined examination was statistically significant (P < 0.05). For patients with dense breast tissue, the differences in diagnostic performance between US and MRI, and between US and the combined examination, were significant (P < 0.05), while the difference between MRI and the combined examination was not significant (P = 0.317).ConclusionMRI and combined examination methods significantly enhance the ability to differentiate benign and malignant breast tumors and provide important clinical value for early breast cancer detection.